Spatial and Temporal Analysis of Quantitative Risk of Flood due to Climate Change in a China’s Plateau Province - Wu, Baolin; Zhang, Zhengtao; Guo, Xinrui; Tan, Cheng; Huang, Chengfang; Tao, Jun (Frontiers in Earth Science, 2022)
The Qinghai-Tibet Plateau is a region sensitive to climate change with significant changes in topography, and the increase of extreme precipitation in the region is easy to lead to landslides and debris flows. To mitigate the effects of climate change, the Chinese government has pledged to an emission reduction target that achieves the ‘carbon peak’ in 2030 and ‘carbon neutral’in 2060 at a huge cost. In order to explore the quantitative flood risk at county-level in Qinghai province (the core province of The Qinghai-Tibet Plateau) and the contribution of emission reduction efforts to risk mitigation, this paper constructs a loss rate curve based on the data of more than 1,000 single flood disasters from 2009 to 2019 through government cooperation and the data of observed cumulative precipitation. Combined with the latest CMIP6 climate model data, the temporal and spatial variation characteristics of the flood loss ratio in Qinghai province from 2020 to 2060 are quantitatively characterized. The results show that :(1) the curve of flood loss rate in Qinghai province from 2020 to 2060 may present a trend of "rising in the early stage, stable in the middle stage, and declining in the late stage" under low (SSP126) and medium (SSP245) emission scenarios, and presents a trend of rising fluctuation under high emission (SSP585) scenario. The flood loss ratio under SSP585 is 10 times higher than that under SSP126; (2) The flood risk of 44 counties from 2020-2060 in Qinghai province may be concentrated in the southeast region, with Jiuzhi county, Banma county, Nangqian county, Gande county and Dari county being the most prominent; (3)Compared with the SSP585, the Qinghai province in SSP126 may cumulatively avoid about 24 billion CNY in economic losses from 2020 to 2060, and avoid nearly 600 million CNY in losses per year which is equivalent to 93% of Qinghai province's special funds for ecological and environmental protection in 2019. The research aims to provide theoretical and data support for flood disaster risk prevention and management in China's high-altitude areas and to promote the initiative of emission reduction in China and even the world.